TEACHER-LED PROFESSIONAL GROWTH: THE REALITY OF BOTTOM-UP TPD AMONG EFL TEACHERS IN INDONESIA - Caecilia Lucky Dewi Purnomo; Paulus Kuswandono (Journal of English Teaching, Applied Linguistics and Literatures (JETALL), 2025)
English teacher professional development in Indonesia has been more top-down and oriented towards administrative fulfilment. However, a bottom-up approach is considered more capable of encouraging meaningful and sustainable professional growth, even though it is still underexplored in Indonesia contexts.  This research aims to explore the reality of bottom-up professional development among EFL teachers in Indonesia, focusing on their strategies to initiate and implement bottom-up TPD and the impact, in conjunction with the challenges and barriers that influence their efforts, especially from institutional and external factors. This research is qualitative employing open-ended questionnaires and semi-structured interviews to collect the data.  The results show that bottom-up TPD works through synergy between personal initiative, collaboration between teachers, technology support, and conducive school environment, which significantly influences changes in teaching practices and teacher professional development. However, teachers also face obstacles in the form of high workload, time constraints, and inconsistent institutional support, so that teacher resilience is an important factor in maintaining the TPD process. This research reveals that bottom-up TPD among English teachers brings more positive results on their teaching practice. In spite of that, the balance depth of narrating the success and failure of bottom-up TPD is still limited.